Examining the social and communal values of urban square towards families and youth - Roslan, Muhammad Ruzaini; Noor Azman, Noor Aqmal Hakim; Zakariya, Khalilah (2014)
Public spaces play a vital role in the cultivation, control and development of communities. Urban Square is an example of public space that, throughout history, has been used as a platform to integrate the community, disseminate and discuss ideas, and enable people of different ages and groups to be part of the public realm. Public urban squares are the new age agoras where innovative and creative designs are expected to accommodate the changing needs of various types of users. Numerous studies have been conducted on the functions and roles of public squares towards the urban environment at large. However, studies on specific types of community and their experiences at the urban square are still scarce. Due to the demanding and constantly changing urban lifestyle, the role of the urban square as a social and communal space has emerged to be significant for urban and suburban dwellers. This study examines on how the community values an urban square in Putrajaya, which is Dataran Putra. Dataran Putra, a public square nestled between the iconic Masjid Putra and the Prime Minister's Office, has grew to become a vibrant and popular public space since its inception in 2001. This study focuses on families and youths to further investigate how they value the square as their social and communal space. Semi-structured interviews and behavioral mapping were employed to collect data about how families’ and youths utilize and value the square as their public space.